Impact of submarine groundwater discharge on fish and zooplankton abundances and on early biofouling processes in a coastal la goon of Tahiti, French Polynesia - Claudia Starke; Werner Ekau; Nils Moosdorf (PANGAEA, 2018)
Submarine groundwater discharge (SGD) in to the sea is widely spread and investigated. However, on the impact of SGD on marine organisms in turn very view work has been done. For a better understanding of the interaction between SGD and its surrounding organisms, the impact of SGD on fish and zooplankton abundances as well as on the early biofouling process was investigated in a coastal la goon of Tahiti, French Polynesia. This study is based on the hypothesis of an enhanced biological production due to increased amounts of nutrient input caused by terrestrial fresh water supply to the sea. Presented data showed a significantly larger growth of algal turfs exposed to the freshwater spring. Plankton evaluations suggest ed slightly higher wet weights and abundances around the freshwater. The implemented stationary photo sampling of fish resulted likewise in a significantly higher fish occurrence around the freshwater spring. The presented data suggest that the elevated nutrient concentrations transmitted by SGD may cause a bottom up control resulting in higher zooplankton and fish abundances around SGD.